(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to identify the concept of legal personality and the meaning of robotic surgery and to identify the possibility of robotic surgery bearing criminal liability. The study used the deductive approach and it study reached several results including that legal personality is the individual’s ability to acquire rights and be obligated to obligations. It was also found that robotic surgery is a programmed robot to perform surgical intervention in the human body. Additionally, there is difficulty in determining the criminal liability of the robot, although it is possible to determine the civil liability of the manufacturer or the medical entity that used the robot in surgery. The study recommended several recommendations including the necessity of enacting criminal legislation that determines the entity or persons criminally responsible for the robot’s actions and setting controls and conditions for granting the robot legal personality and rules of criminal liability arising from its actions.